Pengembangan E-Modul Berbasis AR Pada Pelajaran IPAS Materi Struktur Lapisan Bumi di Kelas V Sekolah Dasar - Zahara, Maulida; Fitrah Dwi, Dara; Rapita Silalahi, Beta; Napitupulu, Safrida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine: 1). produce AR-based E-Modules in science lessons on the material of the structure of the earth's layers. 2). To determine the feasibility of AR-based E-Modules in science lessons on the material of the structure of the earth's layers. 3). To determine the response of teachers and students after the application of AR-based E-Modules in science lessons on the material of the structure of the earth's layers. The method used in this study is the Research and Development (R&D) development method using the 4D model through four stages including: Define, Design, Develop, Dissenimate. The results obtained from several relevant expert validators, namely, module experts get a feasibility score of 97.5%, material experts get a feasibility score of 86%, teacher responses get a feasibility score of 100%, and student responses get a feasibility score of 96.5%. Thus, the AR-based E-Modules in science lessons on the material